(untitled) (Altre Modernità, 2017)
This essay sets out to outline different and frequent types of violation of the traditional and scholastic norm of the Italian language, and to examine doubts and oscillations in its control, in order to explain the origins and reasons – either internal or external to the system – of these “errors” and to highlight the extent of their acceptability in the general use. Obviously, the differences between language modes and levels will be taken into account, especially that between the oral and the written mode. As a result, the distinction between the actual linguistic “error” and its social perception – which has always been crucial in the evolution of languages – will also be restated.